The clinical outcomes and genomic landscapes of acute lymphoblastic leukemia patients with E2A‐PBX1: A 10‐year retrospective study. Issue 11 (4th September 2021) - Zhou, Biqi; Chu, Xinran; Tian, Hong; Liu, Tianhui; Liu, Hong; Gao, Wei; Chen, Suning; Hu, Shaoyan; Wu, Depei; Xu, Yang
Abstract: The clinical outcomes and genomic features of E2A‐PBX1 (TCF3‐PBX1)‐positive B‐cell acute lymphoblastic leukemia (B‐ALL) patients remain unclear. A total of 137 patients carrying E2A‐PBX1 among 3164 B‐ALL patients between 2009 and 2019 were retrospectively analyzed. The 5‐year overall survival (OS) and disease‐free survival (DFS) rates of the whole cohort were 68.6% and 61.0%, respectively. Age [DFS, p = 0.037; cumulative incidence of relapse (CIR), p = 0.005] and the level of minimal residual disease (MRD) after induction chemotherapy (OS, p = 0.020; DFS, p = 0.002; CIR, p = 0.006) were independent risk factors. In adolescents/adults, allogeneic hematopoietic stem cell transplantation (allo‐HSCT) at first complete remission (CR1) significantly improved the 5‐year prognosis (OS, p < 0.001; DFS, p < 0.001; CIR, p < 0.001). Haploidentical HSCT decreased the CIR compared with human leukocyte antigen‐matched HSCT in adolescents/adults ( p = 0.017). Mutations in PBX1, PAX5, CTCF and SETD2, amplification of AKT3, and deletion of CDKN2A/B were common in the total cohort, while transcriptome differences were found in the cell cycle, nerve growth factor (NGF) signaling pathway and transcriptional regulation by TP53 between adolescents/adults and children. Patients with multiple subclones at diagnosis tended to have unfavorable 3‐year prognoses (DFS, p = 0.010; CIR, p = 0.021). Leukemia clones with DNA repair gene mutations showed aggressive and treatment‐refractory phenotypes in this subtype of ALL. Our study indicated that age, the level of MRD and DNA repair gene mutations were associated with E2A‐PBX1‐positive B‐ALL outcomes. Allo‐HSCT, especially haploidentical HSCT, could improve the prognosis of adolescent/adult patients.